A randomised controlled trial of a lifestyle behavioural intervention for patients with low back pain, who are overweight or obese: study protocol. Issue 1 (December 2016) - Williams, Amanda; Wiggers, John; O'Brien, Kate; Wolfenden, Luke; Yoong, Serene; Campbell, Elizabeth; Robson, Emma; McAuley, James; Haskins, Robin; Kamper, Steven; Williams, Christopher
Abstract Background Low back pain is a highly prevalent condition with a significant global burden. Management of lifestyle factors such as overweight and obesity may improve low back pain patient outcomes. Currently there are no randomised controlled trials that have been conducted to assess the effectiveness of lifestyle behavioural interventions in managing low back pain. The aim of this trial is to determine if a telephone-based lifestyle behavioural intervention is effective in reducing pain intensity in overweight or obese patients with low back pain, compared to usual care. Methods/Design A randomised controlled trial will be conducted with patients waiting for an outpatient consultation with an orthopaedic surgeon at a public tertiary referral hospital within New South Wales, Australia for chronic low back pain. Patients will be randomly allocated in a 1:1 ratio to receive a lifestyle behavioural intervention (intervention group) or continue with usual care (control group). After baseline data collection, patients in the intervention group will receive a clinical consultation followed by a 6-month telephone-based lifestyle behavioural intervention (10 individually tailored sessions over a 6-month period) and patients in the control group will continue with usual care. Participants will be followed for 26 weeks and asked to undertake three self-reported questionnaires at baseline (pre-randomisation), week 6 and 26 post randomisation to collect primary and secondary outcome data. The study requires a sample of 80 participants per group to detect a 1.5 point difference in pain intensity (primary outcome) 26 weeks post randomisation. The primary outcome, pain intensity, will be measured using a 0–10 numerical rating scale. Discussion The study will provide robust evidence regarding the effectiveness of a lifestyle behavioural intervention in reducing pain intensity in overweight or obese patients with low back pain and inform management of these patients. Trial registration number Australian New Zealand Clinical Trials Registry, ACTRN12615000478516, Registered 14/05/2015.